2014
DOI: 10.1021/ol500231c
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Direct Arylation of Indoles with Cyclohexanones

Abstract: A novel palladium catalyzed approach to 3-arylindoles was developed from indoles and cyclohexanones. Various cyclohexanones acted as aryl sources via an alkylation and dehydrogenation sequence using molecular oxygen as the hydrogen acceptor. This method showed good regioselectivity and afforded 3-arylindoles as the sole products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(31 citation statements)
references
References 74 publications
1
30
0
Order By: Relevance
“…63 The cyclohexene intermediate was independently synthesized and shown to convert into the aryl-substituted indole product. The cyclohexanones represent arene surrogates, similar to the aryl ether and aniline synthetic routes described above.…”
Section: Pd-catalyzed Dehydrogenation Of Cyclohexenes To Substitutmentioning
confidence: 99%
“…63 The cyclohexene intermediate was independently synthesized and shown to convert into the aryl-substituted indole product. The cyclohexanones represent arene surrogates, similar to the aryl ether and aniline synthetic routes described above.…”
Section: Pd-catalyzed Dehydrogenation Of Cyclohexenes To Substitutmentioning
confidence: 99%
“…45 Treatment of 1-methyl-1H-indole (1a) with 4methylcyclohexanone (2b) in the presence of sulfur powder affords intermediate 1-methyl-3-(4-methylcyclohex-1-en-1-yl)-1H-indole (5a). 21 …”
Section: Under Oxygen Atmosphere This Procedures Provided a Novel Appmentioning
confidence: 99%
“…Although there are other methods available for the construction of 1,2diphenyl-1H-benzo[d] imidazoles, the utilization of cheap and non-aromatic coupling partners under transition-metal-free conditions is rare and challenging. [12] The con-struction of CÀ C, [13] CÀ N, [14] CÀ O, [15] CÀ S [16] bonds as well as heterocycles has been carried out under oxidative conditions in the Deng group. [9] In 2011, S. You et al disclosed a palladium-catalysed cascade amination that allows regiospecific and modular synthesis of a library of structurally diverse 1,2-disubstituted (hetero)aryl fused imidazoles (Scheme 1a).…”
mentioning
confidence: 99%
“…[11] Very recently, Isao et al reported a one-pot method for the selective construction of 1,2-diphenyl-1H-benzo[d] imidazoles involving the dehydro-genation of benzyl alcohols by a π-benzylpalladium(II) system (Scheme 1c). [12] The con-struction of CÀ C, [13] CÀ N, [14] CÀ O, [15] CÀ S [16] bonds as well as heterocycles has been carried out under oxidative conditions in the Deng group. In these transformations, cyclohexanones were used as a versatile aryl source via a dehydrogenation tautomerization sequence.…”
mentioning
confidence: 99%